Between Tort Law, Contract Law, and Child Law: How to Compensate the Left-Behind Parent in International Child Abduction Cases - Schuz, Rhona; Shmueli, Benjamin (Columbia Journal of Gender and Law, 2012)
This Article deals with a unique intersection between civil (tort and/or contract) law, criminal law, family and child law, and international law. Perhaps one of the most traumatic crises that can occur to an individual is having his child abducted by the other parent and taken to another country. The widely ratified 1980 Hague Convention on the Civil Aspects of International Child Abduction is designed to enable the crisis to be resolved as quickly as possible by mandating that the authorities in the state to which the child has been abducted order return of the child to the state of his habitual residence immediately preceding the abduction, unless one of the narrow exceptions in the Convention is established. However, this remedy by itself does not put the left-behind parent in the position he or she was in before the abduction. In particular, the process of recovering the child often places a considerable financial burden on the left-behind parent. For example, he may incur costs in identifying the whereabouts of the child, in traveling to and staying in the state of abduction, and in paying the legal costs of submitting an application for the child’s return in the courts of the requested state. Furthermore, the discovery that his child has been abducted together with the uncertainty as to whether and when he will recover the child and the lack of or reduced contact with the child will often cause considerable emotional distress. The issue of compensation for the left-behind parent is not discussed in the existing literature. This Article examines, therefore, the extent to which it is appropriate to require the abductor to compensate the left-behind parent and the preferred framework for the provision of such compensation. We present four alternative models: the tort model (in which the left-behind parent brings a civil tort claim against the abducting parent), the contract model (in which the left-behind parent brings a civil contract claim against the abducting parent when a contract between the parents has been breached), the criminal model (in which compensation is awarded in criminal proceedings against the abducting parent), and the Abduction Convention model (in which compensation is awarded by the court of the state which is requested to return the child, as part of the proceedings under the Hague Convention). We analyze the advantages and disadvantages of each model from both a theoretical and practical perspective. After concluding that the Abduction Convention model is the preferred model, we discuss various dilemmas that arise in implementing this model and consider how to find an appropriate balance between the objectives of tort law and those of child law, as expressed in the Abduction Convention. Among other considerations, this Article examines the delicate question of whether, in determining the compensation, courts should consider the background of the abduction, and in particular, the relationship between the abductor and the left-behind parent, the relationship between the left-behind parent and the child, contributory negligence or comparative fault on the part of the left-behind parent, the social background of the family, any involvement by the authorities, and the possibility that the abductor has acted out of frustration and despair due to mistreatment by the authorities.